How the brain learns to read - Sousa, David A. (Thousand Oaks, Calif. : Corwin Press, 2005)
Use the power of neuroscience to develop better readers in your class! What must the brain learn in order to read effectively? What has research revealed about phonics and whole language approaches to reading instruction? Arm yourself with the most current neuroscientific information available and start your students down a lifelong path as successful readers. How the brain learns to read presents what scientists have uncovered about how children develop spoken language and use spoken language abilities when learning to read. Best-selling author David Sousa explores source material on brain research and provides scores of practical reading strategies for the K-12 classroom. Complete with relevant brain diagrams and informative tables, this exciting new book examines critical concepts including: understanding language acquisition and its relationship to reading, incorporating modern research findings in your classroom, recognizing and overcoming reading problems, including early intervention programs, content area reading with strategies to improve vocabulary and comprehension, and developing a successful reading program that encourages teachers to be researchers. Reading is essential for success in our society. With this guide to cutting-edge reading research, you'll find the keys to unlocking reading success in your students!
Learning spoken language -- Learning to read -- Teaching reading -- Recognizing reading problems -- Overcoming reading problems -- Reading in the content areas -- Putting it all together.
Includes bibliographical references (p. 225-236) and index.
Keywords: Reading; Reading disability -- Physiological aspects; Brain; Reading; Reading disability -- Physiological aspects; Brain